Low‐level laser (light) therapy (LLLT) for treatment of hair loss. Issue 2 (23rd August 2013) - Avci, Pinar; Gupta, Gaurav K.; Clark, Jason; Wikonkal, Norbert; Hamblin, Michael R.
Abstract Objective Alopecia is a common disorder affecting more than half of the population worldwide. Androgenetic alopecia, the most common type, affects 50% of males over the age of 40 and 75% of females over 65. Only two drugs have been approved so far (minoxidil and finasteride) and hair transplant is the other treatment alternative. This review surveys the evidence for low‐level laser therapy (LLLT) applied to the scalp as a treatment for hair loss and discusses possible mechanisms of actions. Methods and Materials Searches of PubMed and Google Scholar were carried out using keywords alopecia, hair loss, LLLT, photobiomodulation. Results Studies have shown that LLLT stimulated hair growth in mice subjected to chemotherapy‐induced alopecia and also in alopecia areata. Controlled clinical trials demonstrated that LLLT stimulated hair growth in both men and women. Among various mechanisms, the main mechanism is hypothesized to be stimulation of epidermal stem cells in the hair follicle bulge and shifting the follicles into anagen phase. Conclusion LLLT for hair growth in both men and women appears to be both safe and effective. The optimum wavelength, coherence and dosimetric parameters remain to be determined. Lasers Surg. Med. 46:144–151, 2014. © 2013 Wiley Periodicals, Inc.